Evaluation of radon concentration in irrigation and drinking waters from the eastern part of Oman and estimation of effective doses to Omanis - Nasser, Sabeur; Khandaker, Mayeen Uddin; Bradley, David Andrew; Isinkaye, Matthew Omoniyi (Oxford University Press, 2019)
The present study concerns measurement of the radon concentration in drinking and irrigation waters obtained from the eastern part of Oman, in particular in regard to water quality assessment of the region. The samples were collected from different places covering most types of water sources in the region. A passive and time-integrated track etch detector (LR-115 type II) combined with a high-resolution optical microscope has been used to obtain the radon concentration in the studied samples. Values of dissolved radon in water varied among the water sources; the highest concentration of radon was found to be 363 Bq m-3 in a drinking water sample while well water used for irrigation showed the lowest value, at 140 Bq m-3. Measured data for all water sources are below the permissible limit of 11.1 kBq m-3 recommended by the US-EPA. Annual effective doses for the studied samples were in the range 0.38-0.99 μSv y-1 which is significantly less than the action level recommended by the WHO (0.1 mSv y-1), indicating that the water sources in the Jalan BBH region of Oman are safe to use. The obtained data may serve as a reference for any future radiological study of the waterbody of this region. © 2019 The Author(s).